2007
DOI: 10.1103/physrevb.75.024104
|View full text |Cite
|
Sign up to set email alerts
|

Lattice orientation effect on the nanovoid growth in copper under shock loading

Abstract: Molecular-dynamics ͑MD͒ simulations have revealed that under shock loading a nanovoid in copper grows to be of ellipsoidal shape and different loading directions ͓͑100͔ and ͓111͔͒ change the orientation of its major axis. This anisotropic growth is caused by preferential shear dislocation loop emission from the equator of the void under ͓100͔ loading and preferential shear dislocation loop emission deviating away from the equator under ͓111͔ loading. A two-dimensional stress model has been proposed to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Dávila et al [21] carried out molecular dynamics (MD) simulations of void collapse in copper subjected to shock compression, and found that the emission of loops was responsible for the collapse of voids. Zhu et al [22] modeled void growth during release of shock loading in a face-centered cubic (fcc) metal (copper); shear dislocation loop emission from the equator of the void under [1 0 0] loading was observed. Detailed MD calculations by Bringa et al [23] confirmed that shear loop emission is the principal mechanism of void growth in copper; the effects of void size and load orientation were found to be significant, and one-, two-and three-dimensional loop arrangements were identified and analyzed.…”
Section: Introductionmentioning
confidence: 98%
“…Dávila et al [21] carried out molecular dynamics (MD) simulations of void collapse in copper subjected to shock compression, and found that the emission of loops was responsible for the collapse of voids. Zhu et al [22] modeled void growth during release of shock loading in a face-centered cubic (fcc) metal (copper); shear dislocation loop emission from the equator of the void under [1 0 0] loading was observed. Detailed MD calculations by Bringa et al [23] confirmed that shear loop emission is the principal mechanism of void growth in copper; the effects of void size and load orientation were found to be significant, and one-, two-and three-dimensional loop arrangements were identified and analyzed.…”
Section: Introductionmentioning
confidence: 98%
“…Many authors had explored that the micromechanics of void growth is the dislocation loop emission by externally applied stresses, which carry away the material from the void and are responsible for the plastic deformations needed to accommodate significant void growth, e.g., Rudd and Belak (2002), Lubarda et al (2004), Ahn et al (2006), Zhu et al (2007), Traiviratana et al (2008). Modeling of void growth has been studied extensively at the continuum level.…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that the critical stress for nucleation increased for very small voids but did not analyze void growth. Other authors used 3D atomistic simulations to study the nucleation and growth of nm-sized voids [24][25][26][27][28][29][30][31][32] and Potirniche et al [26] reported that smaller voids grew faster at this length scale, a size effect opposed to that found for micrometer-sized voids. However, atomistic simulations of voids growth were limited to very small voids (void radius was below 10 nm) due to the huge computational costs associated with the simulation of larger voids and it is not clear whether the results reported by the analytical and atomistic simulations will hold for larger voids.…”
Section: Introductionmentioning
confidence: 99%